2017
DOI: 10.1186/s12882-017-0451-7
|View full text |Cite
|
Sign up to set email alerts
|

A novel case of renal pathergy reaction in a Behçet’s disease patient complicated by IgA vasculitis

Abstract: BackgroundA pathergy reaction is defined as a hyperreactivity of the skin in response to minimal trauma, which is important in the diagnosis of Behçet’s disease (BD). However, a pathergy reaction may not be restricted to the skin, and little is known about whether an invasive medical procedure can induce the reaction. Here we present a pathergy reaction induced by renal biopsy, an invasive procedure.Case presentationA 46-year-old man who was diagnosed with IgA vasculitis (IgAV) at the age of 38 was treated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Higashihara et al a reported a case of Behçet disease revealed by pathergy reaction induced by renal biopsy, which was masked by the presence of IgA vasculitis, and elucidated the etiology of the unexplainable symptoms [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Higashihara et al a reported a case of Behçet disease revealed by pathergy reaction induced by renal biopsy, which was masked by the presence of IgA vasculitis, and elucidated the etiology of the unexplainable symptoms [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Biopsy may sometimes be required to precisely classify specific renal lesions. However, the unwelcome possibility of a pathergy reaction should be kept in mind [ 49 ].…”
Section: Renal Involvement In Multifactorial Aidsmentioning
confidence: 99%